2019
DOI: 10.1016/j.jmps.2019.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of macroscopic systems with non-vanishing elastic dipole components

Abstract: To simulate a macroscopic system from a simulation cell, a direct summation of the elastic fields produced by periodic images can be used. If the cell contains a non-zero elastic dipole component, the sum is known to be conditionally convergent. In analogy with systems containing electric or magnetic dipoles, we show that the sum introduces a component which only depends on the shape of the summation domain and on the dipole density. A correction to the direct summation is proposed for the strain and stress fi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…Such energy changes are too small to have an appreciable influence on the point defect kinetics. This is in line with a previous study, where stresses of several hundreds of MPa have been shown to be necessary to modify the defect kinetics in Al at 300 K [48]. Since stress effects on diffusion decrease as temperature increases, this validates the approximation of infinite medium for the elastic solution in the present conditions.…”
Section: Application Of the Emission Model: Annealing Of Dislocation ...supporting
confidence: 92%
“…Such energy changes are too small to have an appreciable influence on the point defect kinetics. This is in line with a previous study, where stresses of several hundreds of MPa have been shown to be necessary to modify the defect kinetics in Al at 300 K [48]. Since stress effects on diffusion decrease as temperature increases, this validates the approximation of infinite medium for the elastic solution in the present conditions.…”
Section: Application Of the Emission Model: Annealing Of Dislocation ...supporting
confidence: 92%
“…The elastic interaction between defects can produce spatial ordering [47] and elastic self-pinning of loops [48] , matching experimental TEM observations. But traction-free boundary conditions have also been shown to affect the kinetics of defect coalescence [49] , and the efficiency of defect sinks [50][51][52] . These observations imply the evolution of the nanoscale stress state observed due to defects [53] , and hence the evolution of defect microstructure, must both drive and be driven by component level elastic relaxation [45,54] .…”
Section: Elastic Stress Produced By Radiation Defectsmentioning
confidence: 99%
“…Recently it has been shown that for a box containing an elastic dipole component but no monopole term, the field ε 0 can be written in the following explicit form [48]:…”
Section: Pbcs: Removing the Spurious Dipolar Contributionmentioning
confidence: 99%
“…The field ε 0 is calculated at the centre of the simulation box. In isotropic elasticity, it is convenient to use the analytical form given in [48] and recalled in appendix F. Removing ε 0 amounts to simulating a finite macroscopic system under loading given by σ = −p [48]. This means that to simulate a physical system with free surfaces, this loading should be removed.…”
Section: Pbcs: Removing the Spurious Dipolar Contributionmentioning
confidence: 99%
See 1 more Smart Citation